Trade, Development, and Political Economy in East Asia 2014
DOI: 10.1355/9789814620062-013
|View full text |Cite
|
Sign up to set email alerts
|

7 Exporting, education, and wage differentials between foreign multinationals and local plants in Indonesian and Malaysian manufacturing

Abstract: There is now substantial evidence that foreign multinational enterprises (MNEs) often pay higher wages than corresponding local plants. This paper extends this research by asking whether MNE-local wage differentials depend on whether a plant exports or not. Mean, unconditional, MNE-local wage differentials tended to be somewhat smaller for exporters than for non-exporters in large samples of 11 manufacturing industries of Malaysia in 2000-2004 (31 vs. 44 percent) and Indonesia in 2006 (58 vs. 74 percent), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For 2006, estimates in large samples of all manufacturing plants combined and a few individual industries also reveal positive and significant wage differentials, but many of the industry-level regressions indicate that conditional wage differentials were not significant in the latter year. 1 In addition, analyses of Malaysian plants in 2000-2004 also suggest that conditional wage differentials accounting for both worker education and occupation were positive and significant in most of the individual industries examined and when all sample industries were combined (Ramstetter 2014). Although they do not control for the effects of worker education or occupation, other studies of Malaysia (Lim 1977) and Thailand (Matsuoka-Movshuk and Movshuk 2006;Ramstetter 2004) also found positive and significant wage differentials after controlling for plant-level differences in capital intensity and size, for example.…”
Section: Some Of the Most Comprehensive Analyses Of Wage Differentialmentioning
confidence: 99%
See 1 more Smart Citation
“…For 2006, estimates in large samples of all manufacturing plants combined and a few individual industries also reveal positive and significant wage differentials, but many of the industry-level regressions indicate that conditional wage differentials were not significant in the latter year. 1 In addition, analyses of Malaysian plants in 2000-2004 also suggest that conditional wage differentials accounting for both worker education and occupation were positive and significant in most of the individual industries examined and when all sample industries were combined (Ramstetter 2014). Although they do not control for the effects of worker education or occupation, other studies of Malaysia (Lim 1977) and Thailand (Matsuoka-Movshuk and Movshuk 2006;Ramstetter 2004) also found positive and significant wage differentials after controlling for plant-level differences in capital intensity and size, for example.…”
Section: Some Of the Most Comprehensive Analyses Of Wage Differentialmentioning
confidence: 99%
“…There is a growing literature indicating that foreign-owned multinational enterprises (MNEs) normally pay higher wages than domestic firms in host, developing economies. The most sophisticated studies to date have analysed manufacturing plants in Indonesia and Malaysia, and accounted for the fact that multinational enterprises tend to hire relatively welleducated workers and be relatively large and capital or input intensive compared to local plants (Lipsey and Sjöholm 2004;Ramstetter 2014;Ramstetter and Narjoko 2013). These studies often found positive and significant wage differentials between foreign MNEs and local plants, even after controlling the influences of worker education and sex, as well as plant size and capital intensity.…”
Section: Introductionmentioning
confidence: 99%